Pre-adaptation to noisy Galvanic vestibular stimulation is associated with enhanced sensorimotor performance in novel vestibular environments - Moore, Steven T.; Dilda, Valentina; Morris, Tiffany R.; Yungher, Don A.; MacDougall, Hamish G. (Frontiers in Systems Neuroscience, 2015)
Performance on a visuomotor task in the presence of novel vestibular stimulation was assessed in nine healthy subjects. Four subjects had previously been adapted to 120 minutes exposure to noisy Galvanic vestibular stimulation (GVS) over 12 weekly sessions of 10 minutes; the remaining five subjects had never experienced GVS. Subjects were seated in a flight simulator and asked to null the roll motion of a visual bar presented on a screen using a joystick. Both the visual bar and the simulator cabin were moving in roll with a pseudorandom (sum of sines) waveform that were uncorrelated. The cross correlation coefficient, which ranges from 1 (identical waveforms) to 0 (unrelated waveforms), was calculated for the ideal (perfect nulling of bar motion) and actual joystick input waveform for each subject. The cross correlation coefficient for the GVS-adapted group (0.90 [SD 0.04]) was significantly higher (t[8]=3.162; p=0.013) than the control group (0.82 [SD 0.04]), suggesting that prior adaptation to GVS was associated with an enhanced ability to perform the visuomotor task in the presence of novel vestibular noise.